Adolescents' involvement in decision-making for pediatric weight management: A multi-centre, qualitative study on perspectives of adolescents and health care providers. Issue 6 (June 2019) - Kebbe, Maryam; Perez, Arnaldo; Buchholz, Annick; Scott, Shannon D.; McHugh, Tara-Leigh F.; Richard, Caroline; Dyson, Michele P.; Ball, Geoff D.C.
Highlights: Adolescents and clinicians valued adolescents' involvement in decision-making. Parents influenced the decision-making process in managing adolescent obesity. Adolescents may benefit from individual consultations with clinicians. Abstract: Objective: To explore adolescents' and health care providers' (HCPs) perspectives on adolescents' involvement in decision-making within multidisciplinary clinical care for pediatric weight management. Methods: In this multi-centre, qualitative description study, we purposefully recruited 13-17-year-olds with overweight or obesity and HCPs from two pediatric weight management clinics in Edmonton and Ottawa, Canada. Participants completed one-on-one, in-person, semi-structured interviews (adolescents) or focus groups (HCPs), which were audio-recorded, transcribed verbatim, and managed using NVivo 11 . Data were analyzed by two independent researchers using inductive thematic analysis and the congruent methodological approach for group interactions. Results: A total of 19 adolescents and 16 HCPs participated. Three themes were identified in relation to adolescents' decision-making for weight management, including (i) conditions for adolescent involvement, (ii) preferences for adolescent involvement, and (iii) extent of parental involvement. Conclusions: Although adolescents and HCPs positively valued adolescents' involvement in making decisions regarding their weight and health, the extent to which adolescents wished to be involved in the decision-making process varied between individuals and families. Practice Implications: HCPs are encouraged to include adolescents and families in their health services delivery, including consulting individually with adolescents and tailoring care to their expectations regarding decision-making.